20-HETE: A NEW TARGET FOR THE TREATMENT OF HYPERTENSION - Williams, Jan M. (2010)
Arachidonic acid (AA) is metabolized by enzymes of the CYP4A and 4F families to 20-hydroxyeicosatetraeonic acid (20-HETE) which plays an important role in the regulation of renal function, vascular tone and the long term control of arterial pressure. In the vasculature, 20-HETE is a potent vasoconstrictor and upregulation of the production of this compound contributes to the elevation in oxidative stress, endothelial dysfunction and the increase in peripheral vascular resistance associated with some forms of hypertension. In kidney, 20-HETE inhibits Na(+) transport in the proximal tubule and thick ascending loop of Henle and deficiencies in the renal formation of 20-HETE contributes to sodium retention and the development of some salt-sensitive forms of hypertension. 20-HETE also has renoprotective actions and opposes the effects of transforming growth factor (TGF-β) to promote proteinuria and renal end organ damage in hypertension. Several new inhibitors of the synthesis of 20-HETE and 20-HETE agonists and antagonists have recently been developed. These compounds along with PPAR-α agonists that induce the renal formation 20-HETE appear to have promise as antihypertensive agents. This review summarizes the rationale for the development of drugs that target the 20-HETE pathway for the treatment of hypertension and associated cardiovascular complications.